Indirect Investor Protection: The Investment Ecosystem and Its Legal Underpinnings - Holger Spamann (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
This paper argues that the key mechanisms protecting retail investors' financial stake in their portfolio investments are indirect. They do not rely on actions by the investors or by any private actor directly charged with looking after investors' interests. Rather, they are provided by the ecosystem that investors (are legally forced to) inhabit, as a byproduct of the mostly self-interested, mutually and legally constrained behavior of third parties without a mandate to help the investors (e.g., speculators, activists). This elucidates key rules, resolves the mandatory vs. enabling tension in corporate/securities law, and exposes passive investing's fragile reliance on others' trading.
urn:nbn:de:hebis:30:3-616582
Keywords: G34; G38; K22; 330; Investor Protection; Index Funds; Market Efficiency; Activism; Activist Hedge Fund; Private Equity; Plaintiff Lawyers; Contractarian Model of Corporate Law; Mandatory Law